2019
DOI: 10.19173/irrodl.v20i2.3795
|View full text |Cite
|
Sign up to set email alerts
|

Blending Crowdvoting in Modern e-Learning Environments

Abstract: Given that the most students spend considerable time on social networks, many educational institutions use this habit as a basis for educational purposes. Increasing students’ active participation in learning activities is one of the main goals of education. The purpose of this research was to investigate to what extent crowdvoting techniques can increase students’ participation and interest in the e-learning process. Additionally, we set out to explore social networks as a medium for crowdvoting, contests, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Furthermore, as it is reported that many students engage on social networks for considerable time, educational institutions could use this habit and technology for educational purposes [ 79 ]. Thus, in the implementation of TR, students from G1 and G3 were also required to form groups in an online chat APP (e.g.…”
Section: Empirical Studymentioning
confidence: 99%
“…Furthermore, as it is reported that many students engage on social networks for considerable time, educational institutions could use this habit and technology for educational purposes [ 79 ]. Thus, in the implementation of TR, students from G1 and G3 were also required to form groups in an online chat APP (e.g.…”
Section: Empirical Studymentioning
confidence: 99%